1997
DOI: 10.1023/a:1005704223040
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Heterogeneity in drug sensitivity must, in part, account for the relative lack of success with single agent chemotherapy for glioblastoma multiforme (GBM). In order to develop in vitro model systems to investigate this, clones derived from the VM spontaneous murine astrocytoma have been characterised with regard to drug sensitivity. Six clonal cell lines have been tested for sensitivity to a panel of cytotoxic drugs using an intermediate duration 35S-methionine uptake assay. These lines have previously been ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…During exploitation of the protocol we did not proceed with clonal selection, but instead continued growing and expanding a population of transduced cells. This allowed us to avoid the inter-clonal heterogeneity that is a characteristic of clonal selection 4850 . Validity of this approach was efficiently demonstrated in gene expression and proteomics analyses, in which four independently generated iAstro lines for both WT and 3Tg-AD genotypes were analyzed and gave consistent results, and also demonstrated that 3Tg-iAstro retains the differences as compared with WT-iAstro found previously in primary cultures 40 .…”
Section: Discussionmentioning
confidence: 99%
“…During exploitation of the protocol we did not proceed with clonal selection, but instead continued growing and expanding a population of transduced cells. This allowed us to avoid the inter-clonal heterogeneity that is a characteristic of clonal selection 4850 . Validity of this approach was efficiently demonstrated in gene expression and proteomics analyses, in which four independently generated iAstro lines for both WT and 3Tg-AD genotypes were analyzed and gave consistent results, and also demonstrated that 3Tg-iAstro retains the differences as compared with WT-iAstro found previously in primary cultures 40 .…”
Section: Discussionmentioning
confidence: 99%